Efficacy and Safety of Using Dual Versus Monotherapy Antiplatelet Agents in Secondary Stroke Prevention: Systematic Review and Meta-Analysis of Randomized Controlled Clinical Trials. Issue 25 (30th April 2021) - Trifan, Gabriela; Gorelick, Philip B.; Testai, Fernando D.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Dual antiplatelet treatment (DAPT) with aspirin plus clopidogrel for a limited time is recommended after minor noncardioembolic stroke. Methods: We performed a meta-analysis of all major studies that compared the efficacy and safety of DAPT versus monotherapy for the secondary prevention of recurrent stroke or transient ischemic attack. The primary outcomes were stroke and the composite of stroke, transient ischemic attack, acute coronary syndrome, and death from any cause. The safety outcome was major hemorrhage. Relative risk (RR) and 95% CIs were calculated. Heterogeneity was assessed by I 2 and Cochrane Q statistics. Results: The analysis included 27 358 patients, the quality of evidence was moderate to low, and the heterogeneity for all the comparisons was low ( I 2 ≤25%). Compared with monotherapy, DAPT reduced the risk of recurrent stroke (RR, 0.71 [95% CI, 0.63–0.81]) and composite outcome (RR, 0.76 [95% CI, 0.69–0.83]) but increased the risk of major bleeding (RR, 2.17 [95% CI, 1.45–3.25]). In the subgroup analysis, ≤30 days of DAPT increased the risk of hemorrhage relative to monotherapy (RR, 1.94 [95% CI, 1.08–3.52]). In the sensitivity analysis, the risk for hemorrhage with ≤30 days of DAPT after excluding the combination of aspirin plus ticagrelor was comparable to monotherapy (RR, 1.42 [95% CI, 0.77–2.60]). However, the risk for stroke recurrence and composite outcomes in the subgroup and sensitivity analyses remain decreased compared with monotherapy. Conclusions: DAPT decreases the risk of recurrent stroke and composite events compared with monotherapy. DAPT increases the risk of major hemorrhage, except if the treatment is limited to 30 days and does not include the combination of aspirin plus ticagrelor.